Socioeconomic Status and Educational Choice of the Children in Bangladesh - Abul Kalam Azad (Budapest International Research and Critics University, 2018)
This study aims to predict the educational choice (EC) of children in Bangladesh based on the capital factors of socioeconomic status (CAPSES). For collecting data, the study conducted a survey among the parents selected purposively both from urban and rural areas of Bangladesh. After collecting data, the study used SmartPLS software (Windows Version-3) to analyze both the measurement and structural models. The study findings lead to this proposition that the higher the magnitude of socioeconomic status the parents hold to, the higher the likelihood ratio that they will choose the English medium education for their children and the vice-versa. On the contrary, the lower the magnitude of socioeconomic status the parents hold to, the higher the likelihood ratio that they will choose the madrasa or vocational track of education for their children and vice-versa. Overall, the models have predictive power and relevance (R2=0.684 for EED model, R2= 0.625 for GED model, R2= 0.347 for MED model and R2= 0.298 for VED model).